Anticrisis adaptation strategies of construction enterprises in the process of digital transformation of operational activity - Fesun, A.; Khomenko, O.; Ratnikov, D. (Ways to Improve Construction Efficiency, 2024)
The article explores the management of business processes in construction development under digital transformation and within a multi-project environment. It substantiates an information-based spatio-temporal paradigm, where spatial, temporal, and informational parameters act as determinants of managerial decisions. This paradigm extends beyond financial and technological aspects by incorporating dynamics of spatial change, project chronology, and information flows. Its theoretical foundations combine spatial, institutional, behavioral, and informational economics, enabling interpretation of decision-making under uncertainty and complexity. The study outlines key forms of spatial transformation in construction enterprises: infrastructural, functional, institutional, and social. Their strategic, tactical, and operational manifestations are identified, along with assessment indicators such as building density, index of urban attractiveness, transport accessibility, land value, functional change rates, and the number of development projects. The central contribution is a multi-level methodology of economic-analytical support for risk management in digital transformation. It includes: (1) identification of digitalization risks in multi-project activities; (2) formation of a risk-oriented management model integrating cost, schedule, resources, and digital tools; (3) evaluation of risks’ impact on economic outcomes; (4) construction of an analytical monitoring system with key risk indicators integrated into ERP, CRM, and BIM; (5) development of anti-crisis response and adaptation strategies; (6) institutionalization of risk management within organizational structures; and (7) evaluation of efficiency through quantitative and qualitative metrics. The findings show that the proposed paradigm enhances adaptability to environmental turbulence, reduces financial and managerial risks, balances multi-project portfolios, and accelerates digital modernization. Overall, it provides a scientifically grounded framework for strengthening competitiveness and economic resilience of construction enterprises.